Factors behind the changes in energy intensities of the manufacturing sector in Taiwan - Li, Jing-wen; Chateau, Bertrand; Shrestha, Ram M.; Foell, Wesley K.; Taiwan Cement Company Tai wan, Rep. of China (Bangkok : Asian Institute of Technology, 1988)
Because of its large share of energy consumption, the energy intensity changes of the manufacturing sector have influential impacts on the overall energy consumption in Taiwan, Republic of China . The analysis of the factors behind energy intensity changes of the manufacturing sector is important for formulating economic and energy policies regarding the development of the whole industry. The Divisia index approach is employed in this study to separate the components of the manufacturing energy intensity changes in Taiwan during 1971 - 1985. The manufacturing sector is disaggregated into four groups according to their energy intensities and the classification of ''strategic" and "non strategic" industries in the national economic development plan. The four manufacturing groups are further disaggregated into two digit subgroups. The factors of the changes in energy intensities are decomposed into two main components: the effect of changes in production structure and the effect of changes in subgroup energy intensities. The effect of changes in production structure is further disaggregated into group and subgroup effects. The relations between energy intensities and the labor, capital and multi - factor productivities, as well as between energy intensities and energy prices are also analyzed qualitatively. It is found that improvements in the energy intensities at the 2 - digit industrial subgroup level are the main reasons for the decline in the aggregate energy intensities of the manufacturing sector. Though the structural changes at the four - group level has some contribution to the improvements in energy intensities of the manufacturing sector, the unfavorable sectoral shifts at the 2 - digi t industrial subgroup level make the contribution of structural effects to the improvements in energy intensities of the manufacturing sector not significant.
A thesis submitted in partial fulfillment of the requirements for the degree of Master in Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Industrial districts -- Taiwan; Energy policy -- Taiwan